The relevance of historical geography for Old Testament theology with special reference to Exodus 34:10-26 - Wittenberg, Gunther (Old Testament essays, 1996)
In this paper, the thesis that historical geography is not merely the 'environment' for the development of theology in the Old Testament, but integral to its occurrence, is propounded. It is argued that Exodus 34:10-26 should be interpreted against the background of the 'socio-spatial dialectic' in its theology. This concerns its historico-geographical context and the structuring of 'time-space' in Exodus 34:11-26.